Concise review of the genus Caulerpa J.V. Lamouroux - Zubia, Mayalen; Draisma, Stefano G. A.; Morrissey, Kathryn Lee; Varela-Álvarez, Elena; De Clerck, Olivier (Journal of applied phycology, 2020)
The genus Caulerpa is highly diverse, especially in the Caribbean Sea, the Indo-Malay archipelago and the temperate waters of southern Australia. Currently, more than 100 species are recognized worldwide. Despite recent advances in taxonomy and phylogeny, there is still confusion about the delimitation and identification of some species due to tremendous phenotypic plasticity. Caulerpa is known to occupy a wide range of environmental niches and to have great invasive potential. More studies are necessary to understand better the ecology (invasiveness, the functional role of its microbiome) and the biology (reproduction, life cycle, and metabolism) of Caulerpa species, especially for economical species. Very few species, mainly C. lentillifera and C. racemosa known as green caviar, have been cultivated. Caulerpa is consumed mostly in Asia and Oceania, but its popularity tends to be on the increase in western countries with new nutritional practices (vegetarians, vegans, health foods). Being naturally enriched in essential nutrients and various health-promoting compounds, Caulerpa species are promising candidates for the design of functional foods and in the health and well-being sectors. The diversity of Caulerpa offers a remarkable potential for valorization with innovation opportunities. Caulerpa farming can bring significant economic and environmental (e.g., bioremediation, blue carbon pump) benefits if these farms are established in a sustainable approach.